LINCOLN, NEB., REVISED ORDINANCES, pt. 2, ch. 14, art. 26, § 8 (State Journal Company, Printers 1895). - (:unkn) unknown (General Publisher, 1895)
Prohibited discharging any cannon or artillery in any street, avenue, alley, park, or place within the limits of the city. Violators fined twenty-five dollars.
--
Keywords: DISCHARGE